A thermochromic reversible water-based dye, preparation method and application thereof

The temperature-reversible discolored aqueous dye prepared by paraffin and inorganic layered bimetallic hydroxide (LDHs) intercalation materials solves the problems of insensitive reaction of temperature-repellent and irreversible color changes in the prior art, and achieves accurate and reversible monitoring of the temperature changes of cigarette filter rods.

CN116285942BActive Publication Date: 2025-05-02CHINA TOBACCO YUNNAN IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310269102.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-05-02
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

The temperature-discolored materials used in the prior art to determine the temperature of cigarette filter rods are not sensitive to reactions, and only cause obvious discoloration when the temperature changes greatly, and the color changes are irreversible, making it difficult to accurately predict the temperature.

Method used

The warm-reversible discolored water dye is prepared by using paraffin and inorganic layered bimetallic hydroxide (LDHs) intercalation materials. The paraffin sodium salt and carbonate hydrotalcite are intercalated to form paraffin-carbonate LDHs intercalation materials, which are used on cigarette filter rod forming paper or connecting paper. The color development reaction is reversible under ultraviolet light polymerization.

Benefits of technology

It achieves obvious color changes when the temperature changes are small, and the color changes are reversible, which can accurately predict the temperature changes of cigarette filter rods, and improves the accuracy and reliability of temperature monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285942B_ABST
    Figure CN116285942B_ABST
Patent Text Reader

Abstract

The invention discloses a thermochromic reversible color-changing water-based dye, a preparation method and application thereof, wherein the thermochromic reversible color-changing water-based dye comprises a paraffin-carbonate LDHs intercalation material, wherein the paraffin-carbonate LDHs intercalation material comprises paraffin and hydrotalcite, and the interlayer anion of the hydrotalcite is a carbonate. The invention relates to a paraffin sodium salt and a hydrotalcite to perform an intercalation reaction, thereby obtaining a paraffin-carbonate type hydrotalcite intercalation material, and then using the paraffin sodium salt and the hydrotalcite as a raw material to prepare a water-based dye, and applying the water-based dye to a filter rod forming paper, and after ultraviolet light polymerization, a color change reaction will occur when the temperature rises, and the color will return to the original color after the temperature decreases, and the water-based dye of the invention has excellent color change effect and color change reversibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new materials for cigarettes, in particular to paraffin and inorganic layered double metal hydroxide intercalation dyes, which have an indicating effect on the temperature change of a filter rod during smoking. Background Art

[0002] In the prior art, thermochromic technology is used to cover up the unpleasant yellow and brown color of conventional cigarette paper after heating, or to predict the temperature of cigarette filter rods through color changes.

[0003] During the continuous burning process of cigarettes, their hardness will gradually decrease. At the same time, the clamping and suction actions will exert a certain pressure on them, causing the cigarette to be deformed in shape. This phenomenon is called the thermal collapse of the cigarette filter rod. The thermal collapse of cigarettes seriously affects the appearance of cigarettes, and also causes the suction resistance to increase, making it difficult to smoke. There are many factors that affect the thermal collapse of cigarettes. Among them, the excessively high temperature of the filter rod when the cigarette is smoked is a very important factor. In the prior art, in order to obtain the temperature of the filter rod during the smoking process, some researchers will coat the tipping paper with thermochromic dyes to roughly judge the temperature by color changes. The problem with this method is that most of the thermochromic materials on the market are not sensitive to color. Only when the temperature changes greatly will there be obvious color changes, and it takes a long time for the color change to occur. Secondly, the existing thermochromic materials can only change color at higher temperatures, and the color change difference is not large when the temperature is low. The existing technology of direct hydrotalcite temperature sensing and color display is not sensitive. There will be obvious color change only when the temperature changes greatly, or the color change difference is not large. In other words, the current result of judging the temperature of cigarette filter rods by color display is not very accurate.

[0004] In order to solve the above problems, the present invention is proposed. Summary of the invention

[0005] The full name of LDHs material is layered double hydroxide (LDH) material, which is a general term for hydrotalcite and hydrotalcite-like compounds.

[0006] LDHs materials are relatively common two-dimensional layered materials. The most typical LDHs compound is magnesium aluminum carbonate hydrotalcite, whose chemical composition is: Mg6Al2(OH) 16 CO3·4H2O, its structure is very similar to brucite [Mg(OH)2], which is composed of MgO6 octahedrons sharing edges to form a unit layer. 2+ Can be Al within a certain range 3+ Isomorphous substitution makes the layers positively charged and there is CO3 between the layers 2-The positive charge on the layer plate is balanced, making the overall structure of the LDHs material electrically neutral. The layer plates and interlayer anions of LDHs are connected by hydrogen bonds, which makes the interlayer anions of LDHs materials exchangeable.

[0007] The first aspect of the present invention provides a thermochromic water-based dye, which includes a paraffin-carbonate LDHs intercalation material, wherein the paraffin-carbonate LDHs intercalation material includes paraffin and hydrotalcite, and the interlayer anion of the hydrotalcite is carbonate.

[0008] The second aspect of the present invention provides a method for preparing the thermochromic water-based dye according to the first aspect of the present invention, comprising the following steps:

[0009] (1) preparing sodium paraffin;

[0010] (2) preparing carbonate-type hydrotalcite;

[0011] (3) exchanging the sodium paraffin obtained in step (1) with the interlayer anions of the carbonate-type hydrotalcite obtained in step (2) to obtain a paraffin-carbonate LDHs intercalation material;

[0012] (4) preparing a thermochromic water-based dye using the paraffin-carbonate LDHs intercalation material obtained in step (3) as a raw material.

[0013] Preferably, step (1) of preparing sodium paraffin comprises the following steps:

[0014] (11) mixing paraffin wax with a reaction solvent and reacting the mixture to obtain a reactant;

[0015] (12) The reaction solvent in the reactant is evaporated to dryness, and the obtained solid is dried to obtain a sodium paraffin salt solid.

[0016] Step (11) and step (12) are specifically as follows: (11) adding 100-150 g of paraffin wax solid and 500-600 ml of a 1:1 mixed solution of ethanol / sodium ethanolate to a 1-liter three-necked flask, heating to 78-85° C. on a constant temperature heating table, and stirring for 25-30 minutes to convert the paraffin wax into its sodium carboxylate, that is, converting the carboxyl group at the end of the paraffin wax into a carboxylate anion to form paraffin sodium salt; (12) evaporating the reaction solvent in the reactant with a rotary evaporator, and drying the obtained solid in a vacuum drying oven to obtain a paraffin sodium salt solid.

[0017] Preferably, step (11) is as follows: 100-150g paraffin solid and 500-600ml ethanol and sodium ethoxide mixed in a ratio of 1:1 are mixed, heated to 78-85°C, stirred for 25-30min and reacted, the stirring speed is 500-600rpm, and the reaction time is 40-48h; the drying time in step (12) is more than 5 hours. Preferably, step (2) of preparing carbonate hydrotalcite comprises the following steps:

[0018] (21) Adding deionized water into the autoclave and raising the temperature;

[0019] (22) adding magnesium oxide, aluminum hydroxide and sodium carbonate according to a ratio into the reaction kettle of step (21) and stirring;

[0020] (23) Continue heating to increase the temperature in the reactor. At this time, the pressure in the reactor is the initial pressure. Carbon dioxide gas is introduced into the reactor until the pressure in the reactor reaches 0.7 MPa. When the pressure in the reactor drops back to the initial pressure, continue to introduce carbon dioxide to 0.7 MPa. Repeat the cycle until the total amount of carbon dioxide introduced reaches the required ratio.

[0021] (24) After the feeding is completed, continue the reaction;

[0022] (25) After the reaction is completed, the temperature is lowered, and then the hydrotalcite wet material is obtained by filtering and washing, and then the hydrotalcite wet material is dried to obtain a carbonate hydrotalcite product.

[0023] Preferably, in step (21), the temperature is raised to 80°C; in step (22), the ratio of magnesium oxide: aluminum hydroxide: sodium carbonate is 2:1:0.0015 to 2:1:0.002; in step (23), the temperature in the kettle is raised to 160 to 180°C, the initial pressure is 0.6 MPa, and the total amount of carbon dioxide introduced is carbon dioxide: aluminum hydroxide 25:1; in step (24), the reaction temperature is 150 to 160°C, and the reaction time is 10 to 11 hours; in step (25), the drying temperature is 110 to 120°C, and the drying time is 4.5 to 5 hours.

[0024] Preferably, step (3) comprises: mixing sodium paraffin and LDHs and reacting them, filtering and drying to obtain a paraffin-LDHs intercalation material;

[0025] The reaction conditions are: feed ratio 1:1, stirring speed 500-600 rpm, reaction temperature 60-70°C, reaction time 40-48h; drying temperature 20-30°C, drying time 5-6h.

[0026] Preferably, step (4) is: polyvinyl alcohol, Silok-7170W, Silok-8000 and water are mixed and heated to 50°C and stirred to dissolve, sodium alginate is slowly added under stirring, and after dissolution, it is cooled to room temperature, and paraffin-LDHs intercalation material is added, stirring is continued for 1 hour, ball milling is performed for 8 hours, and then the product is placed at room temperature to air dry to obtain paraffin-LDHs dye.

[0027] The third aspect of the present invention provides an application of the thermochromic reversible water-based dye described in the first aspect of the present invention, which is used on the forming paper or tipping paper of a cigarette filter rod to indicate the temperature change of the filter rod during smoking.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention prepares a powdered dye by intercalating paraffin wax with an inorganic layered double metal hydroxide, and then uses the powdered dye as a coloring material and polyvinyl alcohol, Silok-7170W, Silok-8000, etc. to prepare a water-based dye, and the water-based dye is coated on a forming paper, which not only prevents the lip end from directly contacting the coloring material but also prevents the coloring material from being volatilized and lost due to long-term exposure to the air.

[0030] 2. Hydrotalcite can undergo a color change reaction under ultraviolet polymerization, but the temperature for the color change is relatively high and the color change is irreversible, that is, the color cannot be restored after the temperature is restored. In order to solve this problem, the present invention intercalates sodium paraffin with hydrotalcite to obtain a paraffin-carbonate type hydrotalcite intercalation material, and then uses the paraffin-carbonate type hydrotalcite intercalation material as a raw material to prepare a water-based dye, which is coated on a filter rod forming paper. After ultraviolet polymerization, the color change reaction occurs when the temperature rises, and the color returns to the original color when the temperature is lowered. The water-based dye of the present invention has excellent color change effect and color reversibility.

[0031] 3. Specifically with respect to the preparation method of hydrotalcite and the type of anion, the nitrate-type LDHs synthesized by the alkali method have a hard texture after drying, and the color change is uneven after being prepared into a water-soluble dye. The carbonate-type LDHs prepared by the urea method do not change color significantly after heating, and do not change color significantly after cooling, making it difficult to accurately predict the temperature of the forming paper. The carbonate-type LDHs prepared by the non-urea method change color significantly, but the color development process is irreversible. The paraffin-carbonate-type LDHs intercalated dye obtained by reacting the carbonate-type LDHs prepared by the non-urea method with sodium paraffin has a significant color development effect and a good color recovery effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The color change of carbonate-type LDHs dye upon heating and recovery upon cooling in Example 1;

[0033] Figure 2This is the color change and cooling recovery of the paraffin-nitrate type LDHs intercalated dye in Example 2;

[0034] Figure 3 The color of the paraffin-carbonate LDHs intercalated dye before heating in Example 3;

[0035] Figure 4 This is the color change and cooling recovery of the paraffin-carbonate LDHs intercalated dye in Example 3;

[0036] Figure 5 This is the discoloration effect of the paraffin-carbonate LDHs intercalated dye forming paper coating in Example 3 (before, during and after discoloration). DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the technical solution of the present invention.

[0038] Comparative Example 1: Preparation of carbonate-type LDHs by urea method

[0039] Raw materials: magnesium nitrate, aluminum nitrate, urea, deionized water;

[0040] Feeding amount: magnesium nitrate: aluminum nitrate: urea = 0.04:0.08:1 ratio, add 800 ml of deionized water.

[0041] Reaction conditions: 120°C, 48h.

[0042] Product recovery: After the reaction is completed, remove excess water by suction, wash with deionized water and filter three times, soak in anhydrous ethanol overnight, drain excess ethanol, dry in a vacuum drying oven for 5 hours, and grind into powder with a cyclone mill.

[0043] Comparative Example 2: Alkaline Synthesis of Nitrate-Type LDHs

[0044] Raw materials: magnesium nitrate, aluminum nitrate, anhydrous sodium carbonate, sodium hydroxide.

[0045] Experimental method: 2 parts of magnesium nitrate and 1 part (0.05 mol) of aluminum nitrate were pre-dissolved in 70 ml of deionized water, recorded as solution A; 2 parts of anhydrous sodium carbonate and 0.35 mol of sodium hydroxide were dissolved in 100 ml of deionized water, recorded as solution B; Solution B was slowly dripped (7 ml / min) into the stirring solution A using a dropping funnel, and heating was immediately turned on after the dripping was completed, and stirred in an oil bath at 65°C for 15 hours.

[0046] Product recovery: After the reaction is completed, a paste of hydrotalcite is obtained, excess water is removed by a centrifuge, and the product is washed three times with deionized water and anhydrous ethanol, and excess liquid is removed by a centrifuge. The product is then placed in a vacuum drying oven and dried overnight.

[0047] The hydrotalcite prepared by the method has a hard texture after drying and is ground into powder by a cyclone mill with relatively strong pressure to obtain nitrate-type hydrotalcite.

[0048] Example 1: Preparation of carbonate-type LDHs by non-urea method

[0049] Step 1: Add 25.00 kg of deionized water into a 60 L autoclave and heat to 80 °C;

[0050] Step 2: adding magnesium oxide: aluminum hydroxide: sodium carbonate in a ratio of 2 parts: 1 part: 0.0015 parts into the above reaction kettle and stirring;

[0051] Step 3: Continue heating until the temperature in the reactor reaches 160°C, when the pressure in the reactor is about 0.6Mpa. Introduce carbon dioxide gas into the reactor to 0.7Mpa, and when the pressure drops back to 0.6MPa, continue to introduce carbon dioxide to 0.7MPa, and repeat the cycle in turn. The total amount of carbon dioxide introduced is 1.10kg (25.00mol);

[0052] Step 4: After the feeding is completed, the reaction is continued at 160°C for 10 hours;

[0053] Step 5: After cooling, the hydrotalcite wet material is obtained by filtering and washing, and then dried at 120° C. for 5 h to obtain a carbonate hydrotalcite product.

[0054] Example 2: Preparation of paraffin-nitrate-type LDHs intercalation dye

[0055] Step 1: Preparation of sodium paraffin

[0056] Paraffin wax is mixed with a reaction solvent, the reaction solvent is ethanol, the feed ratio is 1:1.39, the reaction temperature is 60°C, the oil bath is stirred at 500rpm for 48h, and then the solvent is evaporated by a rotary evaporator and placed in a vacuum drying oven for more than 5 hours. Paraffin wax is treated with an ethanol / sodium ethoxide system to convert it into a sodium carboxylate, that is, the carboxyl group at the end of the paraffin wax is converted into a carboxylate anion to form a sodium paraffin salt.

[0057] Step 2: 2 parts of magnesium nitrate and 1 part (0.05 mol) of aluminum nitrate were pre-dissolved in 70 ml of deionized water, which was recorded as solution A;

[0058] Step 3: Add 2 parts of anhydrous sodium carbonate and 0.35 mol of sodium hydroxide into 100 ml of deionized water and dissolve them, which is called solution B.

[0059] Step 4: Use a dropping funnel to slowly drip solution B into the stirring solution A (7 ml / min). Immediately turn on the heating after dripping, stir in an oil bath at 65° C. for 15 h to obtain a paste of hydrotalcite for use.

[0060] Step 5: Use a centrifuge to remove excess water, wash with deionized water and anhydrous ethanol three times respectively, remove excess liquid with a centrifuge again, and place in a vacuum drying oven to dry overnight to obtain paraffin-nitrate type hydrotalcite.

[0061] Example 3: Preparation of paraffin-carbonate type LDHs intercalation dye

[0062] Step 1: Preparation of sodium paraffin

[0063] Paraffin was mixed with a reaction solvent, the reaction solvent was ethanol, the feed ratio was 1:1.39, the reaction temperature was 60°C, the oil bath was stirred at 500rpm for 48h, and then the solvent was evaporated with a rotary evaporator and placed in a vacuum drying oven for more than 5 hours. Paraffin was treated with an ethanol / sodium ethanol system to convert it into a sodium carboxylate, that is, the carboxyl group at the end of the paraffin was converted into a carboxylate anion to form a sodium paraffin salt. In order to exchange the anions between the LDHs material layers in Example 1.

[0064] Step 2: Preparation of paraffin-carbonate LDHs intercalation material

[0065] Take a portion of the product of Example 1, add 200 ml of water, and subject to ultrasonic vibration for 10 minutes to form a carbonate hydrotalcite dispersion to obtain a carbonate-type hydrotalcite intercalation material.

[0066] The product paraffin sodium salt in Example 1 was mixed with LDHs in Example 1 at a feed ratio of 1:1, and stirred in an oil bath at 500 rpm and 60°C for 48 hours. The corresponding paraffin-LDHs intercalation material was obtained by suction filtration and drying. During the preparation process, paraffin and LDHs underwent an intercalation reaction, that is, the carboxylate anions of the paraffin replaced the interlayer carbonate ions (CO3 2- ).

[0067] During the preparation process, paraffin wax and LDHs undergo intercalation reaction, and the carboxylate anions of paraffin wax replace the interlayer anions (CO3 2- ). Obviously, the solubility of paraffin carboxylate ions in water is extremely poor. In comparison, the solubility of the interlayer anions of the LDHs materials in Comparative Example 1, Comparative Example 2, and Example 1 is better in water. The difference in solubility of the two ions in water is the driving force of this reaction.

[0068] The hydrotalcite or paraffin-hydrotalcite intercalated dye prepared in the comparative example and the example was used as a coloring raw material to prepare a water-based coating according to the following method, and the obtained water-based coating was printed on a forming paper, and its color change effect and color change reversibility were examined.

[0069] 1. Preparation of water-based coatings

[0070] Raw materials: polyvinyl alcohol 088-05, sodium alginate, hydrotalcite or paraffin-hydrotalcite intercalated dye prepared in comparative examples and examples, Silok-7170W (dispersant), Silok-8000 (wetting agent), deionized water;

[0071] Preparation method: Take 10g polyvinyl alcohol, 0.2g Silok-7170W, 0.2g Silok-8000, and appropriate amount of water, heat to 50°C and stir to dissolve, slowly add 1g sodium alginate under stirring, cool to room temperature after dissolution, add 10g hydrotalcite or paraffin-hydrotalcite intercalated dye prepared in comparative examples and examples, add deionized water to make up the balance to 100g, stir for 1h, and ball mill for 8h. After air drying at room temperature, the products are different water-based coatings.

[0072] 2. UV polymerization

[0073] UV polymerization, apply the water-based coating to the filter paper, irradiate with 254nm UV light for 1-2min, place in a ventilated place to dry naturally for 24h, and cut and put on a plate.

[0074] 3. Reversible color change effect test

[0075] During the UV polymerization process, observe and record the color change, then heat the irradiated product with a hot air gun, observe and record the color change; take it out of the oven, let it stand and let it cool naturally, observe and record the color change; repeat the heating-cooling-heating-cooling process, observe and record its reversible color change performance.

[0076] The color development effects of the above-mentioned comparative samples and example samples were tested, and the results are as follows:

[0077] (1) Comparative Example 1: Preparation of carbonate-type LDHs by urea method

[0078] Color change effect: The color change is not obvious after heating up, and the color change is not obvious after cooling down.

[0079] (2) Comparative Example 2: Alkaline Synthesis of Nitrate-Type LDHs

[0080] Color change effect: The hydrotalcite prepared by the method has a hard texture after drying, and the color change effect of the water-soluble dye prepared by the method is more obvious than that of comparative example 1, but the color change is uneven and the color is inconsistent after heating.

[0081] (3) Example 1: Non-urea carbonate-type LDHs

[0082] The prepared carbonate LDHs intercalated powder is blue ( Figure 1 Left in the middle), after UV polymerization, the color changes when heated to 150°C, and after repeated heating and returning to room temperature, it turns purple-black ( Figure 1 This is because a small part of the powder changes color to dark purple after being heated, which is irreversible. Therefore, no water-soluble dye was prepared and the forming paper coating could not be carried out.

[0083] (4) Example 2: Paraffin-nitrate-type LDHs intercalation dye

[0084] Paraffin-nitrate-type LDHs intercalation dye is originally pink ( Figure 2 Left), it turns into blue-purple after ultraviolet light, and after high-temperature baking, it becomes bright orange ( Figure 2 Middle picture), remove the heat source, and cool to obtain purple-red ( Figure 2 Right), and this effect can be achieved through multiple heating-cooling cycles. However, the paraffin-nitrate LDHs intercalation dye is similar to the nitrate LDHs, with a hard texture and uneven color change. In addition, the color of the paraffin-nitrate LDHs intercalation dye before and after the color change is relatively close in color system, and it is not easy to observe subtle changes.

[0085] (5) Example 3: Paraffin-carbonate type LDHs intercalation dye

[0086] like Figure 5 As shown, after 254nm ultraviolet light irradiation, the paraffin-LDHs intercalated dye changes from pink ( Figure 3 ) turns blue-purple ( Figure 4 Left), after heating, it changes from blue-purple to rose-red ( Figure 4 Middle picture), remove the heat source and cool to room temperature, the color first returns to blue-purple ( Figure 4 The color change effect is obvious and reversible, and it can return to blue-purple. In addition, compared with paraffin-nitrate-type LDHs intercalation dyes, the color of paraffin-carbonate-type LDHs intercalation dyes before and after color change is clearly distinguished, and subtle changes are easy to observe.

[0087] In order to verify the uniformity of large-area color change of paraffin-carbonate LDHs intercalated dye, the dye was coated on the forming paper using an offline coating process, and the coating was polymerized by irradiation with a UV curing machine and fixed in a blast drying oven with a clip. 2 The printing volume is printed according to the preset pattern to a quantitative value of 25g / m2 On the forming paper base paper; UV polymerization: UV polymerization, apply the water-based coating to the filter paper, irradiate with 254nm UV light for 1-2min, place it in a ventilated place to dry naturally for 24h, cut and put it into a tray to obtain thermochromic forming paper or tipping paper.

[0088] Use a blast drying oven to heat to different temperatures (40℃~100℃), maintain the temperature for 10 minutes after reaching the set temperature, so that the temperature inside the oven reaches a stable state, observe and record the color change; open the oven door, cool for 2~3 minutes, observe and record the color change after cooling. Figure 5 , which is consistent with the results on the filter paper, the filter paper printed with the water-based coating of paraffin-LDHs intercalated material has an original color of blue-purple after UV polymerization. After heating, it changes from blue-purple to rose red. When the heat source is removed and cooled to room temperature, the color first returns to blue-purple. The color change effect is obvious and reversible, and the color change uniformity over a large area is good.

[0089] Comparison of thermal stability between reversible color changing forming paper and filter rod:

[0090] After preparing the filter rod using the formed paper coated with the water-based coating of the paraffin-LDHs intercalation material, the filter rod was placed in a blower to observe the temperature change. By smoking 150 cigarettes, the temperature and color development were observed. The observation results are shown in Table 1:

[0091] Table 1 Comparison of temperature and color development

[0092]

[0093]

[0094] In summary, the nitrate-type LDHs synthesized by the alkali method of the present invention have a hard texture after drying, and the color change is uneven after being prepared into a water-soluble dye. The color change of carbonate-type LDHs prepared by the urea method is not obvious after heating, and the color change is not obvious after cooling, and it is difficult to accurately predict the temperature of the forming paper. The color change of carbonate-type LDHs by the non-urea method is obvious, but the color development process is irreversible. Paraffin-nitrate-type LDHs intercalation dye is similar to nitrate-type LDHs, with a hard texture and uneven color change. In addition, the color of the paraffin-nitrate-type LDHs intercalation dye before and after color change is relatively close in color system, and it is not easy to observe subtle changes. The paraffin-carbonate-type LDHs intercalation dye obtained by the reaction of carbonate-type LDHs prepared by the non-urea method and sodium paraffin has obvious color development effect and good color recovery effect. In addition, the color of the paraffin-carbonate-type LDHs intercalation dye before and after color change is clearly distinguished, and subtle changes are easy to observe.

Claims

1. A thermochromic water-based dye, characterized in that: The invention comprises a paraffin-carbonate LDHs intercalation material, wherein the paraffin-carbonate LDHs intercalation material comprises paraffin and hydrotalcite, and the interlayer anion of the hydrotalcite is carbonate. The preparation method of the thermochromic reversible water-based dye comprises the following steps: (1) preparing sodium paraffin, comprising the following steps: (11) mixing paraffin wax with a reaction solvent and reacting the mixture, specifically, mixing 100-150 g of paraffin wax solid and 500-600 ml of a mixture of ethanol and sodium ethoxide in a ratio of 1:1, heating the mixture to 78-85° C., stirring the mixture for 25-30 min, and reacting the mixture at a stirring speed of 500-600 rpm for a reaction time of 40-48 h to obtain a reactant; (12) evaporating the reaction solvent in the reactant and drying the obtained solid for more than 5 hours to obtain a sodium paraffin solid; (2) preparing carbonate hydrotalcite, comprising the following steps: (21) Deionized water was added to the autoclave and the temperature was raised to 80°C; (22) adding magnesium oxide, aluminum hydroxide and sodium carbonate into the reaction kettle of step (21) and stirring according to the ratio of magnesium oxide: aluminum hydroxide: sodium carbonate = 2:1:0.0015 to 2:1:0.002; (23) Continue heating to raise the temperature in the reactor to 160-180° C., at which time the initial pressure of the reactor is 0.6 MPa, and introduce carbon dioxide gas into the reactor until the pressure of the reactor reaches 0.7 MPa. When the pressure of the reactor drops back to the initial pressure, continue to introduce carbon dioxide to 0.7 MPa, and repeat the cycle until the total amount of carbon dioxide introduced reaches carbon dioxide: aluminum hydroxide = 25:1; (24) After the feeding is completed, the reaction is continued at a temperature of 150-160° C. and a reaction time of 10-11 h; (25) After the reaction is completed, the temperature is lowered, and then the hydrotalcite wet material is obtained by filtering and washing, and then the hydrotalcite wet material is dried at a drying temperature of 110 to 120° C. and a drying time of 4.5 to 5 h to obtain carbonate-type hydrotalcite; (3) exchanging the sodium paraffin obtained in step (1) with the interlayer anions of the carbonate-type hydrotalcite obtained in step (2) to obtain a paraffin-carbonate LDHs intercalation material, specifically: The sodium paraffin obtained in step (1) and the carbonate-type hydrotalcite obtained in step (2) are mixed and reacted, and then filtered and dried to obtain a paraffin-LDHs intercalation material; The reaction conditions are: sodium paraffin: carbonate hydrotalcite = 1:1, stirring speed is 500-600 rpm, reaction temperature is 60-70°C, reaction time is 40-48h; drying temperature is 20-30°C, drying time is 5-6h; (4) Using the paraffin-carbonate LDHs intercalation material obtained in step (3) as a raw material, a thermochromic water-based dye is prepared, specifically: polyvinyl alcohol, Silok-7170W, Silok-8000, and water are mixed, and heated to 50-60° C. and stirred to dissolve, sodium alginate is slowly added under stirring, and after dissolution, it is cooled to room temperature, and the paraffin-LDHs intercalation material is added, and stirring is continued for 1.0-1.2 hours, ball milling is performed for 8-8.5 hours, and then the product is placed at room temperature to air-dry to obtain the thermochromic water-based dye.

2. A thermochromic water-based dye according to claim 1, characterized in that: In step (4), the ratio of polyvinyl alcohol, Silok-7170W, Silok-8000, sodium alginate and paraffin-LDHs intercalation material is 50:1:1:5:

50.

3. An application of a thermochromic water-based dye according to claim 1, characterized in that: It is used on the forming paper or tipping paper of cigarette filter rods to indicate the temperature change of the filter rod during smoking.

Citation Information

Patent Citations

  • Method for predicting thermal collapse condition and residual puff number in cigarette smoking process

    CN116297656A